Development of 10 L mass culture system of human induced pluripotent stem cells with intermittent agitation using plastic fluid - Tokura, Tomohiro; Yamamoto, Riku; Kino-oka, Masahiro (Frontiers in Bioengineering and Biotechnology, 2025)
Human induced pluripotent stem cells (hiPSCs) are crucial for cell therapy and regenerative medicine. The development of high-yield and stable mass-culture technologies is essential for the industrialization of hiPSCs. In this study, we proposed a design procedure for the scale-up of hiPSCs and evaluated a mass culture system at a 10 L scale, which is currently challenging. We developed a design procedure for a hiPSC aggregate culture system based on cell manufacturability. Considering the biological aspects, including not only cell behavior but also aggregate behavior, the input variables of the engineering aspects were identified. To mitigate the hydrodynamic force of the fluid flow caused by agitation, we proposed intermittent agitation using a plastic fluid. This method maintained the oxygen supply and aggregate dispersion with minimal agitation using fluid plasticity. Moreover, designing mass cultures requires the establishment of aseptic processing. We developed a single-use bioreactor and closed system, along with a medium exchange and preparation process to ensure aseptic processing. After designing the mass culture system, small-scale model experiments were carried out using a 1 L bioreactor. In three independent trials, the specific growth rate of hiPSCs was found to be similar to that of the conventional small stirred bioreactor. In addition to the above-mentioned culture design, the addition of a Rho-associated coiled-coil containing protein kinase (ROCK) inhibitor was required to maintain the aggregate structure at the 10 L scale. We stably performed 10 L cultures three times, and the specific growth rate was comparable to that on the 1 L scale. The final cell number of hiPSCs reached (1.09 ± 0.02) × 1010 cells. These findings provide a procedure for scaling up the design and contribute to the development of mass culture systems that ensure reproducible and stable hiPSC cultures.